2004
DOI: 10.1021/jp0368482
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization of 2-Bromo-2-Chloro-1,1,1-Trifluoroethane (Halothane) and Hexafluoroethane for Nonbonded Interactions

Abstract: Ab initio and empirical methods were combined to optimize the partial atomic charges and Lennard-Jones parameters for two halogenated compounds, halothane (CF3CHClBr, a potent volatile anesthetic) and hexafluoroethane (CF3CF3, a nonanesthetic). Charge optimization was achieved using empirical calculations by systematically adjusting the charge assignments to fit minimum interaction energies and geometries between a TIP3 water molecule and the halogenated compounds to the corresponding values from the ab initio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 41 publications
4
47
0
Order By: Relevance
“…That theoretical investigation [3] concluded that access to the H-atom in Halothane is hindered by adjacent voluminous halogens, and no evidence for CHÁ Á Áhalogen bonding was found. More recent theoretical studies suggested that H-donor properties and formation of weak hydrogen bonds between Halothane and methanol, dimethyl ether, and in other complexes are possible [6][7][8][9]. In this study we found that the highly positive H-atom (Fig.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…That theoretical investigation [3] concluded that access to the H-atom in Halothane is hindered by adjacent voluminous halogens, and no evidence for CHÁ Á Áhalogen bonding was found. More recent theoretical studies suggested that H-donor properties and formation of weak hydrogen bonds between Halothane and methanol, dimethyl ether, and in other complexes are possible [6][7][8][9]. In this study we found that the highly positive H-atom (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…Medical applications of Halothane were intensively studied, but no structural studies were carried out. It is a liquid with low boiling point of 325 K [2] and only the energy minimization and ab initio calculations were performed to obtain the structure and properties the isolated molecule of this compound [3][4][5][6][7][8][9]. The theoretical studies on the intermolecular interactions and H-donor properties of Halothane and other anesthetics, and their ability to form complexes with other compounds were not conclusive-initially they suggested no H-donor properties for Halothane [3], whereas most recent results showed that weak hydrogen bonds involving the CH group can be formed [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The halothane and HFE [2,3] concentrations were about 5 mol% in the lipid bilayers. The simulation procedures are the same as previously reported [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…The basic setup of the simulations follows previous work [1,9]. After initial minimization, the systems were equilibrated for 1 ns, followed by a production phase of 5 ns with time steps of 1 fs.…”
Section: Simulationsmentioning
confidence: 99%
“…(1-fluoroethane, 1,1-difluoroethane, and 1,1,1-trifluoroethane) [8] and by Liu et al (hexafluoroethane and halothane) [9]. Both groups fitted parameters to liquid density and enthalpy of vaporization data, reporting deviations from experimental data within 2%.…”
Section: Force Field Parametersmentioning
confidence: 99%